Advancing sustainable rice production in the Vietnamese Mekong Delta insights from ecological farming systems in An Giang Province - Tran, Dung Duc (2024)
Rice serves as a crucial staple food crop for half of the world's population. In the Vietnamese Mekong Delta (VMD), rice production plays a vital role in national food security. However, the majority of the existing intensified rice cultivation schemes in the VMD, which are typically traditional, have rendered many farmers' livelihoods unsustainable due to issues such as land degradation, water pollution, health risks, and low profitability. Therefore, it is imperative to explore alternative sustainable farming systems. This study investigates the benefits of two ecological farming systems, specifically organic rice and rice mixed with lotus, as alternatives to conventional rice farming in the upper VMD floodplain province of An Giang. These two farming systems have demonstrated long-term socioecological and economic advantages. On the one hand, they allow the introduction of rice products to the market at more affordable prices. Additionally, they contribute to improved water quality, improved soil fertility, and increased biodiversity such as bird, fish, and plant species compared to traditional rice farming systems. Although we acknowledge that the availability of floodwater poses a significant constraint for alternative farming systems, the business opportunities and socioecological benefits associated with these systems outweigh the limitations. Our findings provide evidence that ecological farming practices that support rice cultivation represent promising alternatives to sustainable rice production, which can help mitigate vulnerabilities in intensified rice farming systems and can be scaled up for other floodplain provinces in the VMD and beyond.